2021
DOI: 10.4196/kjpp.2021.25.6.575
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on the diurnal patterns of gut microbial composition in male and female mice

Abstract: Composition of the gut microbiota changes with aging and plays an important role in age-associated disease such as metabolic syndrome, cancer, and neurodegeneration. The gut microbiota composition oscillates through the day, and the disruption of their diurnal rhythm results in gut dysbiosis leading to metabolic and immune dysfunctions. It is well documented that circadian rhythm changes with age in several biological functions such as sleep, body temperature, and hormone secretion. However, it is not defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…It was found in this study that treatment with SIA significantly reduced the relative abundance of Helicobacter and Alloprevotella , which is dominant in some age‐induced diseases 60 . As previous report that Alloprevotella was not detected in young female mice but was present in high levels in aged female mice 61 . Alistipes , Ligilactobacillus , and Lachnospiracae_NK4A136_ groups are also associated with inflammation, and the latter is negatively associated with inflammation 62,63 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It was found in this study that treatment with SIA significantly reduced the relative abundance of Helicobacter and Alloprevotella , which is dominant in some age‐induced diseases 60 . As previous report that Alloprevotella was not detected in young female mice but was present in high levels in aged female mice 61 . Alistipes , Ligilactobacillus , and Lachnospiracae_NK4A136_ groups are also associated with inflammation, and the latter is negatively associated with inflammation 62,63 .…”
Section: Discussionsupporting
confidence: 80%
“…60 As previous report that Alloprevotella was not detected in young female mice but was present in high levels in aged female mice. 61 Alistipes, Ligilactobacillus, and Lachnospira-cae_NK4A136_ groups are also associated with inflammation, and the latter is negatively associated with inflammation. 62,63 In the present study, the relative abundance of Lachnospira-cae_NK4A136_ groups was significantly reduced and that of the Alistipes and Ligilactobacillus was significantly changed after SIA intervention, which indicated that SIA might delay skin aging by alleviating inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…8 E demonstrates the representative genera with significant changes between tumor group and normal group. Lachnospiraceae UCG- 001 has been reported to be more abundant in older female mice than in younger females, suggesting that it is associated with aging [ 43 ]. Prevotellaceae_UCG-001 is associated with the pathogenesis of colitis [ 44 ].…”
Section: Resultsmentioning
confidence: 99%